Pulsatile Dexamethasone in Patients with Infantile Spasms: A Retrospective Analysis of a Unique Therapy Regime - Reimer, Dennis; Brandl, Ulrich; Vries, Heike De (Neuropediatrics, 2025)
Objective Infantile spasms (IS) are an age-specific epilepsy syndrome associated with poor outcomes. Sustained and early spasm control remains the main goal of therapy. We aimed to evaluate a unique pulsatile dexamethasone therapy regime in children with IS.Methods Children with IS were treated with oral pulsatile-applied dexamethasone in the Children's Hospital Jena between 2002 and 2021, regardless of duration since IS onset or previous therapy (except ACTH). A prolonged initial pulse was given in case of insufficient response (standard: 5–7 days, prolonged: 10–14 days). We analyzed spasm reduction, electroencephalographic response, adverse reactions, neurodevelopmental status, and epileptic disorders at the last follow-up.Results Included were 26 patients with a median age of 5.5 months (interquartile range 4–8) at IS onset and a mean follow-up of 6.2 years (standard deviation [SD] 3.99). Fifty percent had an unknown etiology. Patients received on average 10.8 pulses (SD 6.0); 69.2% achieved initial seizure freedom, however, 38.9% relapsed. Seventeen patients had an initial prolonged pulse, of those, 14 got initially seizure-free (82.4%). Sixty-four percent of the cases had a sustained spasm cessation after the third pulse. At the last follow-up, half of the patients had no persisting epileptic disorder; 22.2% had a favorable neurocognitive development. Patients with unknown etiology were more likely to achieve seizure freedom during therapy (p = 0.025), had a more favorable neurocognitive outcome (p = 0.049), and were less likely to suffer from epileptic disorders (p = 0.037). No serious adverse effects were observed.Conclusion Our results show that our treatment is safe and leads to outcomes comparable to usually applied hormonal therapy regimes. Etiology remains the most influential factor.
Keywords: west syndrome; infantile spasms; pulsatile therapy; dexamethasone; corticosteroids